Eyesight and Imaging : Advances and New Perspectives - Ziaei, Alireza; Lanza, Michele; Ziaei, Alireza; Lanza, Michele (IntechOpen, 2021)
Science and research have always been crucial to furthering our understanding of ophthalmic conditions and their treatment and prevention. Scientific achievements in ophthalmology have produced fundamental insights and opened up possibilities for improving human health. This book provides readers with a comprehensive overview of the latest and most advanced findings in several aspects of ophthalmic pathology, treatment, and surgical strategies, as well as in vision sciences and perception. Chapters cover such topics as acute hydrops, cataract treatments, keratoconus, surgical/non-surgical treatments in vision rehabilitation, and geometric analysis of ophthalmic lens.
English
Keywords: Ophthalmology